KEABSAHAN KLAUSULA EKSONERASI PADA PERJANJIAN BAKU DALAM PERSPEKTIF HUKUM ISLAM - muadil faizin (Istinbath : Jurnal Hukum, 2017)
The current development, instant culture, and efficient dos in every activity of business, need to use the standaard contract. It is believed that businessmen make the standard exoneratie clause unilaterally and the consumer don’t have choices for doing negotiation or bergaining position, when make transactions. For example; the eksemsi clause, the determination of the interest clause, the entire immediate payment clause of financial lease, the forbidding returned item clause of buying, the risky clause, the delayed clause in transportation, the clause of forbidding brought food in karaoke business. Based on the desctiption, this article will explore The Validity Of Clauses Of The Standaard Contract In The Perspective Of Islamic Law. This article explores the fundamental of the legal agreement, the legal culture of Indonesia, and the fundamental of the Islamic law agreement. This article rediscovers that the fundamental of the Islamic law agreement is the ibahah fundamental, the free fundamental, the consented fundamental, the pact fundamental, the balance fundamental, the beneficial fundamental, the honest fundamental, and the fair fundamental. This article stresses that the standaard contract is ably, because corresponding to the ibahah fundamental and the free fundamental. But the clauses weren’t corresponding to the free fundamental, the consented fundamental, the balance fundamental, the beneficial fundamental, the honest fundamental, and the fair fundamental. Consequently, the validity of the clauses isn’t fulfilled. Perkembangan zaman, budaya instan dan upaya efisiensi dalam setiap kegiatan bisnis, mengharuskan untuk penggunaan perjanjian baku. Umumnya perusahaan membuat klausula eksonerasi perjanjian baku secara sepihak dan pihak konsumen tidak memiliki kesempatan untuk melakukan negosiasi atau tawar menawar ketika melakukan transaksi. Sebagai contohnya; klausula eksemsi, klausula penetapan bunga, klausula pembayaran seluruh seketika dalam sewa beli, klausula barang tak boleh dikembalikan dalam jual beli, klausula risiko (cacat dalam leasing dan kehilangan dalam jasa parkir), klausul penundaan jadwal di bidang transportasi, dan klausula larangan membawa makanan dalam usaha karaoke. Berdasarkan uraian tersebut, tulisan ini akan membahas keabsahan klausul eksemsi pada perjanjian baku dalam perspektif hukum Islam. Tulisan ini mengkaji asas-asas hukum perjanjian konvensional, budaya hukum Indonesia, dan asas-asas perjanjian dalam hukum Islam. Tulisan ini menemukan bahwa asas perjanjian hukum Islam meliputi; asas ibahah, asas kebebasan, asas konsensualisme, asas janji mengikat, asas keseimbangan, asas kemaslahatan, asas amanah, dan asas keadilan. Tulisan ini menegaskan bahwa pada dasarnya perjanjian baku boleh, sebab sesuai dengan asas ibahah dan asas kebebasan. Namun klausul eksemsi tidak sesuai dengan asas kebebasan, asas konsensualisme, asas keseimbangan, asas kemaslahatan, asas amanah dan asas keadilan. Sehingga dapat dinilai bahwa keabsahan klausula eksemsi tidak terpenuhi.